Processes developed for the separation of europium (Eu) from various resources. Issue 2 (3rd April 2019) - Kumari, Archana; Jha, Manis Kumar; Pathak, Devendra Deo; Chakravarty, Sanchita; Lee, Jae-chun
Abstract : Europium (Eu), one of the most significant rare earth (RE) elements, has wide applications as functional material in phosphor production, majorly used in fluorescent lamps, computer monitors, televisions etc. Eu is one of the three divalent lanthanides (along with Yb and Sm) having a reduction potential higher than −2 V. This possibility of Eu reduction is attributed to a relatively stable half-filled 4f 7 electronic configuration, thus providing a high stabilization energy and selective recovery. But the Eu recuperation from natural minerals is either accompanied with other REs or Eu is recovered as a group of light REs. Selective recovery of Eu has sparked the progress for its reutilization through recycling of secondary resources. The perspectives of reclaiming Eu as a value added product from various sources using different pyro-hydro or hybrid techniques are discussed. The systematic research and salient findings on methods, viz., reduction, leaching, solvent extraction, as well as combined methods scaled-up to commercial scale to recover Eu, are also reported with recommendations. Thus, this comparative as well as summarized review hopes to help researchers to develop feasible processes for Eu recovery.